Machinability of Nano-Structured Biomaterials for Dental Implants - Stancekova, Dana; Semcer, Jan; Holubjak, Jozef; Drbul, Mario (Communications - Scientific letters of the University of Zilina, 2014)
High quality materials are characterized by increased wear resistance, high strength and hardness, abrasive wear resistance, heat and creep resistance. Due to these properties some materials are considered as hard to machine. This group of materials includes biocompatible materials used for manufacturing implants from commercially pure titanium TiGr2, TiGr5, nano-structured commercially pure titanium nTi and volume-formed titanium alloy TiNbTa. Materials were tested by milling operations with different cutting parameters and force of cutting monitoring.